Penggunaan Media Pembelajaran Bowling Match Pada Siswa Kelas VIII di SMP Negeri Banda Aceh - Dhea Rizki Avista; Ruslan; Hasbi Ali (Jurnal Ragam Pengabdian, 2026)
This study examines the use of game-based learning media in improving the quality of Civic Education (PPKn) learning. The problems identified include the low level of student participation and cognitive learning outcomes at SMP Negeri 8 Banda Aceh, where conventional teaching methods still dominate and the use of learning media such as bowling match has not been optimized. This research employed a qualitative approach with a descriptive design. Data were collected through structured interviews with two Civic Education teachers and eight eighth-grade students, and then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the use of bowling match learning media was able to increase student engagement, motivation, and understanding, while also creating a more interactive and enjoyable learning atmosphere. However, several obstacles were found, including limited classroom space, students’ initial lack of understanding of the game rules, and challenging classroom management. Therefore, bowling match learning media is considered effective as an innovative learning alternative, especially when supported by proper management and adjustments to learning conditions.